2000
DOI: 10.3928/0022-0124-20000901-05
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of AIDS Continuing Education on Psychiatric and Non-Psychiatric Nurses' Knowledge

Abstract: Background: Because an increasing number of chronically mentally ill individuals are HIV-positive, continuing education must include AIDS content to ensure psychiatric nurses provide competent care. The Fundamentals of Mental Health and HIV/AIDS Program was tested to determine its effectiveness in augmenting the AIDS knowledge of mental health professionals. Method: Two hundred forty RNs attended the Fundamental of Mental Health and HIV/AIDS Program. They completed pretest and posttest measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Early in the HIV/AIDS epidemic, education received by nurses was primarily related to transmission, contagion, and infection control agency policies with little education focused on homosexuality, bisexuality, and specific care of PWAs such as symptom management, psychosocial, spiritual, legal, or financial issues . More recently, Dancy, Despotes, Razzano, and Cook (2000) found that nurses who attended an educational program about the fundamentals of mental health and HIV/AIDS continued to find crucial aspects of nursing care about the management of HIV disease and the psychological aspects of the grieving process lacking in nursing education.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Early in the HIV/AIDS epidemic, education received by nurses was primarily related to transmission, contagion, and infection control agency policies with little education focused on homosexuality, bisexuality, and specific care of PWAs such as symptom management, psychosocial, spiritual, legal, or financial issues . More recently, Dancy, Despotes, Razzano, and Cook (2000) found that nurses who attended an educational program about the fundamentals of mental health and HIV/AIDS continued to find crucial aspects of nursing care about the management of HIV disease and the psychological aspects of the grieving process lacking in nursing education.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Several previous studies document that the barriers limiting health workers' role as HIV prevention leaders can be overcome. Training that emphasizes social learning and skill building has been shown to increase HIV-related sensitivity (Hewitt, 1993;Selwyn, 1998;Dancy, Despotes, and Razzano, 2000). A recent study in Nigeria found that an intervention that included information, role modelling, and discussion of stigma and human rights significantly reduced health workers' fears and improved their attitudes and perceived counselling and treatment skills in the intervention state compared to a control state (Ezedinachi et al, 2002).…”
Section: The Challenge Of Aids and The Health Care Systemmentioning
confidence: 99%
“…All trainings included segments delivered by “peers,” defined as individuals with mental health difficulties and/or individuals living with HIV/AIDS. Evaluation of 1600 participants in the Fundamentals curriculum (Linsk et al, 2002; Dancy, Despotes, Razzano & Cook, 2000) revealed significant improvements in trainees’ overall knowledge levels from pretest to posttest.…”
Section: Methodsmentioning
confidence: 99%